Outcome of Darunavir–Cobicistat-Based Regimens in HIV-Infected People Who Have Experienced Virological Failure - Alberton F; Galli L; Lolatto R; Candela C; Gianotti N; Chiurlo M; Ranzenigo M; Strano M; Uglietti A; Castagna A (Dove Medical Press, 2024)
Francesca Alberton,1 Laura Galli,2 Riccardo Lolatto,2 Caterina Candela,1 Nicola Gianotti,2 Matteo Chiurlo,2 Martina Ranzenigo,2 Martina Strano,2 Alessia Uglietti,3 Antonella Castagna1,2 1Infectious Diseases Unit, Vita Salute San Raffaele University, Milan, Italy; 2Infectious Diseases Unit, San Raffaele Scientific Institute, Milan, Italy; 3Medical Affairs Department, Infectious Diseases and Vaccines & Rare Diseases, Johnson&Johnson, Milan, ItalyCorrespondence: Alessia Uglietti, Medical Affairs Department, Infectious Disease and Vaccines & Rare Diseases, Johnson&Johnson, viale Fulvio Testi 280/6, Milan, 20126, Italy, Tel +39-344 2665502, Email augliett@its.jnj.comObjective: To evaluate the virological outcome of darunavir-cobicistat (DRVc)‐based regimens in adults living with HIV who had experienced virological failure (VF) on any previous drug combination.Methods: This was a retrospective cohort study (CSLHIV Cohort) of adults living with HIV who started a DRVc‐based regimen with HIV‐RNA > 50 copies/mL after VF on any previous drug combination. Data on demographics, antiretroviral treatment since HIV diagnosis, and immunological and metabolic parameters from baseline (start of DRVc) to 48 weeks were analyzed in order to assess the cumulative proportion of those who achieved virological success (VS), defined as at least one instance of HIV‐RNA < 50 copies/mL within 12 months from baseline. Follow-up lasted from the start of the DRVc-based regimen (baseline) to the first instance of HIV-RNA < 50 copies/mL, last available visit, or loss to follow‐up or death, whichever occurred first. Univariate and multivariate Cox proportional-hazard regression models were used to identify baseline factors associated with VS.Results: A total of 176 individuals were included, and 120 (68.2%) achieved < 50 HIV‐RNA copies/mL within 12 months since baseline. On multivariate analysis, baseline HDL cholesterol was independently associated with the occurrence of VS (adjusted HR 1.021, 95% CI 1.004- 1.038; p=0.014). Among the 120 subjects with VS, 27 (22.5%) had had VF during a median follow-up of 20.8 months since the first undetectable HIV-RNA. Resistance testing after VF was available in two cases, which harboured the HIV variant-bearing protease inhibitor-resistance mutations D30N, I50V, and N88D. During a median follow-up of 38.4 months, 65 of 176 (36.9%) individuals discontinued DRVc for any reason (37 of 120, 30.8%) and achieved VS vs. 28 of 56 (50%) without VS (p=0.019). Time to discontinuation was longer in people with VS (41.5 vs. 23.0 months, p=0.0007). No statistically significant changes were observed in immunological or lipid profiles during follow-up.Conclusion: Most individuals in this study achieved VS within 12 months from the beginning of a DRVc-based regimen; therefore, this treatment represent a viable option for people who have experienced VF on other regimens.Keywords: HIV infection, antiretroviral therapy, ART, darunavir-cobicistat, DRVc, virological failure, VF